SOMBOR INDEX OF LINE AND TOTAL GRAPHS AND PERICONDENSED BENZENOID HYDROCARBONS - Li, Yue; Ren, Qingcuo; Liang, Jinxia; Yang, Chengxu; Tong, Qinghe (International Journal of Research -GRANTHAALAYAH, 2022)
Gutman proposed a new alternative interpretation of vertex-degree-based topological index, called Sombor index. It is defined via the term . In this paper, we determine the explicit expressions of Sombor index for line and total graphs and several pericondensed benzenoid hydrocarbons.